Dorcus liyuani Qi & Zhan, a new stag beetle from Gansu, China (Coleoptera: Lucanidae: Lucaninae) - Qi, Zhi-Hao; Zhan, Zhi-Hong; Su, Rong-Xiang; Ding, Bi; Liang, Guang-Hong; Song, Hai-Tian (Zootaxa, 2025)
In this study, a new stag beetle of the genus Dorcus MacLeay, 1819 is described and illustrated, namely Dorcus liyuani Qi & Zhan, new species, from Gansu Province, northwestern China. The new species is very similar to its related species, especially D. tianlongi Wang & Zhou, 2019 and D. liyingbingi Huang & Chen, 2013, in external characters, but can be clearly distinguished by male genital features. There is also a clear geographical isolation between the new species and the closely related species.